Effects of the deletion of chemical agent washout on operations at the Blue Grass Chemical Agent Destruction Pilot Plant (The National Academies Press, 2016)
"The United States manufactured significant quantities of chemical weapons during the Cold War and the years prior. Because the chemical weapons are aging, storage constitutes an ongoing risk to the facility workforces and to the communities nearby. In addition, the Chemical Weapons Convention treaty stipulates that the chemical weapons be destroyed. The United States has destroyed approximately 90 percent of the chemical weapons stockpile located at seven sites. Due to public opposition to the use of incineration to destroy the BGAD stockpile, Congress mandated that non- incineration technologies be identified for use at BGCAPP. As a result, the original BGCAPP design called for munitions to be drained of agent and then for the munition bodies to be washed out using high-pressure hot water. However as part of a larger package of modifications called Engineering Change Proposal 87 (ECP-87), the munition washout step was eliminated. Effects of the Deletion of Chemical Agent Washout on Operations at the Blue Grass Chemical Agent Destruction Pilot Plant examines the impacts of this design change on operations at BGCAPP and makes recommendations to guide future decision making"--Publisher's description